2023
DOI: 10.3389/fphar.2023.1129874
|View full text |Cite
|
Sign up to set email alerts
|

Coicis Semen for the treatment of malignant tumors of the female reproductive system: A review of traditional Chinese medicinal uses, phytochemistry, pharmacokinetics, and pharmacodynamics

Abstract: CoicisSemen is an important food product and traditional Chinese medicine (TCM) derived from the dried and mature seeds of Coix lacryma-jobi L.var.ma-yuen (Roman.) Stapf. An increasing number of studies have investigated its use, either alone or in combination with other botanical drugs, to treat female reproductive system malignancies, and its pharmacological effects have been confirmed clinically. This review aims to provide an overview of Coicis Semen’s historical role in treating female reproductive system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…Cinnamaldehyde, tetrahydropalmatine, rhein, and 6‐gingerol are auxiliary ingredients. Among these, ephedrine hydrochloride has various pharmacological effects, including antitussive, expectorant, anti‐inflammatory, neuroprotective, cardiovascular protection, antiandrogenic, and anticancer properties (Dang et al, 2023). Ephedrine hydrochloride is known for its cough‐suppressing, bronchial‐dilating, bronchodilatory, central stimulating, hypotensive, and hypoglycemic effects (Zheng et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Cinnamaldehyde, tetrahydropalmatine, rhein, and 6‐gingerol are auxiliary ingredients. Among these, ephedrine hydrochloride has various pharmacological effects, including antitussive, expectorant, anti‐inflammatory, neuroprotective, cardiovascular protection, antiandrogenic, and anticancer properties (Dang et al, 2023). Ephedrine hydrochloride is known for its cough‐suppressing, bronchial‐dilating, bronchodilatory, central stimulating, hypotensive, and hypoglycemic effects (Zheng et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Huang et al [ 12 ] discussed the chemical composition, anticancer mechanisms, marketed drugs, dosage forms, and clinical applications of fatty oils, including coix seed and other plants. Pan et al [ 65 ] only discusses the treatment of malignant tumors in the female reproductive system with coix seed. This article discusses the anti-tumor effect of coix seed and is not limited to malignant tumors in the female reproductive system.…”
Section: Discussionmentioning
confidence: 99%
“…Fingerprinting of Coicis semen from dried tissues using the sequence-independent microarray ( Niu et al, 2013 ) and the high-performance liquid chromatography (HPLC)-evaporative light scattering detector ( Du et al, 2021 ) has been reported. It contains more than 80 active components including polysaccharides, fatty acids (FAs), phenolic acids, sterols, lipids, flavonoids, triterpenes, alkaloids, and adenosine ( Zhu, 2017 ; Yu J. et al, 2022 ; Huang et al, 2022 ; Pan et al, 2023 ; Wei et al, 2023 ). The HPLC-atmospheric pressure chemical ionization-mass spectrometry (MS) method identified 12 triacylglycerols in coix oil ( Xiang et al, 2005 ).…”
Section: The Cardiovascular Protective Activity Of Yyfzmentioning
confidence: 99%
“…The chromatographic fingerprint revealed the main pharmacologically active ingredients of Coicis semen, including 1,3-Dioleoyl-2-palmitoylglycerol, 1,2-dilinoleoyl-3-oleoyl-rac-glycerol, 1,3-Dipalmitoyl-2-Linolein, 1,2-Dilinoleoyl-3-palmitoyl-rac-glycerol, 1,2-Dioleoyl-3-linoleoyl-rac-glycerol, and glycerol trioleate ( Du et al, 2021 ). These components are primarily responsible for improving lipid metabolism, antioxidation, and anti-inflammation, providing analgesic effects, and offering cardiovascular protection ( Zhu R. et al, 2020 ; Chen et al, 2022 ; Yang et al, 2022d ; Zeng et al, 2022 ; Pan et al, 2023 ), thereby supporting proper heart function and protecting against CVD ( Xu et al, 2017 ; Chen et al, 2022 ). Studies have shown that Coicis semen has positive effects on CHDs ( Yu F. et al, 2011 ; Wang et al, 2012 ), atherosclerosis ( Check and K'Ombut, 1995 ; Yu F. et al, 2011 ), myocardial ischemia, MI( Yu J. et al, 2022 ), hypertension ( Li et al, 2017 ; Chen et al, 2020 ), hypercholesterolemia ( Wang et al, 2012 ), and hyperlipidemia ( Chen et al, 2022 ).…”
Section: The Cardiovascular Protective Activity Of Yyfzmentioning
confidence: 99%